PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tutia Rahmi; Tertiarto Wahyudi; Rochmawati Daud (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2018)
The purpose of this research is to explain the effect of financial performance to the stock return. The financial performances in this research were Earning Per Share, Price Earning Ratio, Debt to Equity Ratio, Return On Assets, andNet Profit Margin. The financial performance as the independent variables and the dependent variabel is stock return.The sample of this research is thirty manufacturing company of consumer goods industry sector. These companies are listed on the Indonesia Stock Exchange since 2012 until 2014. The sampling method is purposive sampling. The analysis method used in this research that is with hypothesis test that is determinant coefficient, test F, and test t. Using thirty manufacturing companies listed in IDX, this research shows that the Earning Per Share, Price Earning Ratio and the Net Profit Margin has a positive and significant impact on stock returns. Instead, the variable Debt to Equity Ratio has a negative influence. This research also indicate that variable Return On Assets has no effect on stock returns.